Beyond Cosmopolitanism Towards Planetary Transformations (Springer Singapore, 2018)
Considering the different traditions of cosmopolitan thinking and experimentation, this cutting edge volume examines the contemporary revival of cosmopolitanism as a response to the challenges of living in an interdependent world. Through a unique multidisciplinary approach, it takes the debate beyond the one-sided universalism of the Euro-American world and explores the multiverse of transformations which confront cosmopolitanism. The collection highlights central questions of cosmopolitan responsibility, global citizenship and justice as well as the importance of dialogue among civilizations, cultures, religions and traditions. Exploring the ethical and political dimensions of globalization, it outlines the pathways of going beyond cosmopolitanism by striving for a post-colonial cosmopolis characterized by global justice, trans-civilizational dialogues and dignity for all.